MEDICINAL PLANTS USED FOR TREATMENT OF DIABETES BY THE MARAKH SECT OF THE GARO TRIBE LIVING IN MYMENSINGH DISTRICT, BANGLADESH - Rahmatullah, Mohammed; Azam, Md. Nur Kabidul; Khatun, Zubaida; Seraj, Syeda; Islam, Farhana; Rahman, Md. Atiqur; Jahan, Sharmin; Aziz, Md. Shah; Jahan, Rownak (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Diabetes mellitus is an endocrinological disorder arising from insulin deficiency or due to ineffectiveness of the insulin produced by the body. This results in high blood glucose and with time, to neurological, cardiovascular, retinal and renal complications. It is a debilitating disease and affects the population of every country of the world. Around 200 million people of the world suffer from this disease and this figure is projected to rise to 300 million in the coming years. The disease cannot be cured with allopathic medicine as the drugs used do not restore normal glucose homeostasis and moreover have side-effects. On the other hand, traditional medicinal practitioners of various countries claim to cure diabetes or at least alleviate the major symptoms and progression of this disease through administration of medicinal plants. The Garos are an indigenous community of Bangladesh, who still follow their traditional medicinal practices. Their traditional medicinal formulations contain a number of plants, which they claim to be active antidiabetic agents. Since observation of indigenous practices have led to discovery of many modern drugs, it was the objective of the present study to conduct a survey among the Marakh sect of the Garos residing in Mymensingh district of Bangladesh to find out the medicinal plants that they use for treatment of diabetes. It was found that the tribal practitioners of the Marakh sect of the Garos use twelve medicinal plants for treatment of diabetes. These plants were Lannea coromandelica, Alstonia scholaris, Catharanthus roseus, Enhydra fluctuans, Terminalia chebula, Coccinia grandis, Momordica charantia, Cuscuta reflexa, Phyllanthus emblica, Syzygium aqueum, Drynaria quercifolia, and Clerodendrum viscosum. A review of the scientific literature demonstrated that almost all the plants used by the Garo tribal practitioners have reported antidiabetic and/or antioxidant properties and have enormous potential for possible development of new and efficacious antidiabetic drugs.